Effects of Repeated Use and Sterilization on the Wear of Zirconia Implant Drills: A SEM‐Based Analysis - Vasilios Alevizakos; Richard Mosch; Ann‐Christin Platte; Constantin vonSee (Clinical and Experimental Dental Research)
ABSTRACT Objectives This study evaluated the effects of repeated use and sterilization on the wear and cutting‐edge integrity of zirconia implant drills. Materials and Methods Sixty zirconium dioxide drills (Z‐Systems AG) with diameters of 2.3, 3.75, and 4.25 mm were tested. Drilling was performed in porcine mandibular bone under standardized conditions: 800 rpm, 50 Ncm torque, and 20 N axial pressure. Drills were divided into two groups: Group 1 (sterilized but unused) and Group 2 (30 drilling cycles with reprocessing). Wear was assessed using scanning electron microscopy (SEM) at 1000x magnification, applying a three‐grade scoring system. Statistical analysis was performed using the Mann–Whitney U test (p < 0.05). Results Drills subjected to 30 cycles showed significantly higher wear grades (Grade 2–3) compared to unused drills (Grade 0–1) (p < 0.001). The mean wear grades increased from 0.3 to 2.6 for 2.3 mm, from 0.4 to 2.7 for 3.75 mm, and from 0.2 to 2.7 for 4.25 mm drills. Effect sizes (r = 0.88–0.90) confirmed a strong relationship between repeated use and wear. Conclusions Zirconia drills show significant wear after 30 cycles. Although they offer potential as an alternative to steel drills, further research is needed to optimize cost‐effectiveness and clinical durability. Clinical Trial Registration Not applicable.